Starotestamentowe życie nienarodzonych - Wojciech Węgrzyniak (Polonia Sacra)
The article aims to analyze the Old Testament’s idea of life before birth. Firstly, I examine some expressions describing sexual intercourse. Secondly, I study the meaning of the word הרה hārāh “to conceive”. Thirdly, I analyze some crucial texts (ad es. Rdz 25, 21– 24; Wj 21, 22–25; Hi 10; Ps 139). At the end, I offer a brief synthesis of the Old Testament’s idea about life between conception and birth.